2016
DOI: 10.7755/fb.114.4.2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of density and length of Pacific groundfishes observed from 2 survey vehicles: a manned submersible and a remotely operated vehicle

Abstract: Abstract-Visual surveys of seafloor communities in deep water are becoming more common and provide fishery-independent abundance estimates that could improve stock assessments for some groundfish species. However, limitations of the survey vehicle must be considered when developing methods. To that end, we estimated densities of demersal fishes from 28 paired strip-transect surveys, using a manned submersible (a human-occupied vehicle, HOV) and a remotely operated vehicle (ROV) in 3 types of habitats (high-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The use of AUVs has evolved from anecdotal “that's cool” curiosity—basically “RUVs” (recreational underwater vehicles)—to nondestructive quantitative visual survey tools (Sward et al, 2019). From in situ crewed submarine surveys and later adding video systems to uncrewed ROVs, fishery scientists and marine geologists have collaborated to observe the relationship between demersal species and physical and geological features and ultimately map fish density and biomass throughout the benthic marine habitat (Laidig & Yoklavich, 2016). Starting with coarse spatial scales, submersible surveys evolved to identifying resident fish on rock outcrops with 1 m accuracy, documenting strong fidelity of individual fish to an outcrop.…”
Section: Quantifying Fish and Other Marine Populationsmentioning
confidence: 99%
“…The use of AUVs has evolved from anecdotal “that's cool” curiosity—basically “RUVs” (recreational underwater vehicles)—to nondestructive quantitative visual survey tools (Sward et al, 2019). From in situ crewed submarine surveys and later adding video systems to uncrewed ROVs, fishery scientists and marine geologists have collaborated to observe the relationship between demersal species and physical and geological features and ultimately map fish density and biomass throughout the benthic marine habitat (Laidig & Yoklavich, 2016). Starting with coarse spatial scales, submersible surveys evolved to identifying resident fish on rock outcrops with 1 m accuracy, documenting strong fidelity of individual fish to an outcrop.…”
Section: Quantifying Fish and Other Marine Populationsmentioning
confidence: 99%
“…The authors speculated that these differences could be due to the presence of a tether on the ROV (absent from the HOV), differences between the ROV and HOV in the positioning of lighting (forward versus starboard, respectively), difference in sounds emitted by the vehicles, and the difference in the size of the vehicles. Following up on this work [ 23 ], these researchers compared fish diversities, densities, and sizes obtained during this same study. They found that 1) density estimates of taxa associated with the seafloor were higher in the HOV surveys, 2) a greater percentage of HOV-observed fishes could be sized, and 3) a higher percentage of fishes in the HOV surveys could be identified to species.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have compared ROV with Autonomous underwater vehicles (AUVs) and manned submersibles, despite employing similar methodology. In a study comparing the abundances and lengths of fish collected by ROV and manned submersible surveys across different habitats and depths in California, manned submersibles were able to record a greater number of species, body length estimates, and abundances of species that were found closer to the seafloor (Laidig and Yoklavich, 2016). While the number of studies comparing these methods are limited, ROVs are a more practical and inexpensive tool for monitoring (Koenig et al, 2005), and possess greater maneuverability than AUVs and manned submersibles.…”
Section: Methods Comparison Studiesmentioning
confidence: 99%